2022
DOI: 10.1111/peps.12558
|View full text |Cite
|
Sign up to set email alerts
|

Simply the best? Star performers and high‐potential employees: Critical reflections and a path forward for research and practice

Abstract: In recent decades, scholars' and practitioners' interest in star performers and high-potential employees (HiPos) has increased dramatically. To date, however, researchers have considered these two classifications of exceptional talent in relative isolation of one another, despite the fact that they are widely considered to comprise organizations' most valuable employees. The current article identifies and explores key intersections in the heretofore-siloed streams of research on star employees and HiPos. In so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 142 publications
0
13
0
Order By: Relevance
“…Studies have identified nuanced effects that can stem from employees’ success at work, such as greater victimization (Campbell et al, 2017; Jensen et al, 2014) and contingent impact on peers’ performance (e.g., Downes et al, 2021). Special treatment of high performers has typically been viewed through a strategic lens to recruit and retain them (Kehoe et al, 2022; Rousseau et al, 2006). However, to our knowledge, little research has considered whether high performers also enjoy more favorable evaluations within the domain of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified nuanced effects that can stem from employees’ success at work, such as greater victimization (Campbell et al, 2017; Jensen et al, 2014) and contingent impact on peers’ performance (e.g., Downes et al, 2021). Special treatment of high performers has typically been viewed through a strategic lens to recruit and retain them (Kehoe et al, 2022; Rousseau et al, 2006). However, to our knowledge, little research has considered whether high performers also enjoy more favorable evaluations within the domain of ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Considering talent through a matching lens can advance the consideration of talent beyond traditional binary talent definitions, allowing a broader approach to defining and managing talent (Kehoe et al., 2022). Implementing matching requires a greater focus on the different jobs (and required skillsets) in an organization and simultaneously identifying different types of talent, such that the definition of talent expands beyond the core talent pool while recognizing that other employees could also possess valuable skills or potential for contributions at any time point.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the research on stars virtually ignored this question, with a greater focus on output and productivity as an outcome, not on the characteristics that determine it. In summary, although many of the articles failed to address this dimension, paradox thinking offers significant potential as a lens through which to create value (see also Kehoe et al., 2022).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations